L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Occupational Integration in Healthcare by French-speaking Immigrants Living in Minority Communities - Goss Gilroy Inc. (GGI) (2020)
This report presents the results of a research project on the occupational integration of French speaking immigrants in healthcare, in Francophone minority communities. Through interviews, this project examines the challenges faced by French-speaking immigrants working or pursuing a career in the health sector in Nova Scotia, Ontario and Alberta. Researchers also mobilized literature on the occupational integration of immigrants, data from the 2016 Census and the results of quantitative studies. The research shows that the need for English language skills constitutes a major obstacle at various stages of French-speaking immigrants’ occupational integration journey. The interviews also indicate that employment assistance services in French are not equipped to deal with the complex trajectories of internationally educated health professionals, or to help them identify alternative careers. During internships or at the start of employment, supports in French promoting the integration of immigrants (through mentoring, training workshops for employers, etc.) are very limited. Recommendations are addressed to the Department of Immigration, Refugees and Citizenship Canada and aim to improve supports offered to the study population from the start of their migration project to retention in their workplace.